2022
DOI: 10.3390/biology12010011
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Pattern of the GRAS Gene Family in Pitaya (Selenicereus undatus L.)

Abstract: The GRAS gene family is one of the most important families of transcriptional factors that have diverse functions in plant growth and developmental processes including axillary meristem patterning, signal-transduction, cell maintenance, phytohormone and light signaling. Despite their importance, the function of GRAS genes in pitaya fruit (Selenicereus undatus L.) remains unknown. Here, 45 members of the HuGRAS gene family were identified in the pitaya genome, which was distributed on 11 chromosomes. All 45 mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 77 publications
1
0
0
Order By: Relevance
“…The 82 EgrGRAS genes were classified into nine subfamilies based on evolutionary relationships, including PAT1, SHR, LISCL, HAM, SCR, RGL, LAS, DELLA and SCL3. Consistent with the previous reports, the LISCL and SHR subfamilies did not contain GRAS genes from soybean [ 35 ]. The phylogenetic tree showed that most of the EgrGRAS proteins were classified into the same evolutionary branches as Arabidopsis or soybean, suggesting homology in their evolutionary relationships.…”
Section: Discussionsupporting
confidence: 92%
“…The 82 EgrGRAS genes were classified into nine subfamilies based on evolutionary relationships, including PAT1, SHR, LISCL, HAM, SCR, RGL, LAS, DELLA and SCL3. Consistent with the previous reports, the LISCL and SHR subfamilies did not contain GRAS genes from soybean [ 35 ]. The phylogenetic tree showed that most of the EgrGRAS proteins were classified into the same evolutionary branches as Arabidopsis or soybean, suggesting homology in their evolutionary relationships.…”
Section: Discussionsupporting
confidence: 92%